EKTRAKSI ZAT WARNA ALAM DARI KAYU ULIN (Eusideroxylon zwageri), KAYU SECANG (Caesalpinia sp) DAN KAYU MENGKUDU (Morinda citrifolia) UNTUK BAHAN WARNA KAIN SASIRANGAN - Rinne Nintasari; Desi Mustika Amaliyah (Kementerian Perindustrian, 2016)
Natural Dyes Extraction from Ulin Wood (Eusideroxylon zwageri), Secang Wood (Caesalpinia sp ) and Noni Wood (Morinda citrifolia ) for SasiranganNatural dyes have a beautiful and distinctive color that hard to imitate with synthetic colors. Natural dyes have been recommended as a dyes that safe for the environment and human health. It contains natural components that relatively low pollution load, easily biodegradable and non-toxic. The aim of this research is to identify the adsorption of natural dyes from ulin wood (Eusideroxylon zwageri), secang wood (Caesalpinia sappan) and mengkudu wood (Morinda citrifolia) to cotton and satin material by extrac and soaking processes. The results of organoleptic test showed that people prefers dyed satin than dyed cotton because the dyed colour in satin is brighter than in. The adsorption of dye in satin ranges from 1.81% to 5.68%, while in cotton ranges from 1.35% to 1.93%. The results showed that fabric with smaller size of fiber/yarn will have a higher colour adsorbtion rate because the dyes are easier to adsorb.Keywords: extraction, natural dyes, fabric, sasirangan